PC4 serves as a negative regulator of skin wound healing in mice. Issue 1 (5th May 2020) - Liao, Fengying; Chen, Long; Luo, Peng; Jiang, Zhongyong; Chen, Zelin; Wang, Ziwen; Zhang, Chi; Wang, Yu; He, Jintao; Wang, Qing; Wang, Yawei; Liu, Lang; et al.
Abstract: Background: Human positive cofactor 4 (PC4) was initially characterized as a multifunctional transcriptional cofactor, but its role in skin wound healing is still unclear. The purpose of this study was to explore the role of PC4 in skin wound healing through PC4 knock-in mouse model. Methods: A PC4 knock-in mouse model (PC4 +/+ ) with a dorsal full-thickness wound was used to investigate the biological functions of PC4 in skin wound healing. Quantitative PCR, Western blot analysis and immunohistochemistry were performed to evaluate the expression of PC4; Sirius red staining and immunofluorescence were performed to explore the change of collagen deposition and angiogenesis. Proliferation and apoptosis were detected using Ki67 staining and TUNEL assay. Primary dermal fibroblasts were isolated from mouse skin to perform cell scratch experiments, cck-8 assay and colony formation assay. Results: The PC4 +/+ mice were fertile and did not display overt abnormalities but showed an obvious delay in cutaneous healing of dorsal skin. Histological staining showed insufficient re-epithelialization, decreased angiogenesis and collagen deposition, increased apoptosis and decreased cell proliferation in PC4 +/+ skin. Our data also showed decreased migration rate and proliferation ability in cultured primary fibroblasts from PC4 +/+ mice in vitro . Conclusions: This study suggests that PC4 might serve as a negative regulator of skin wound healing in mice.